Pulmonary toxicity of molybdenum disulphide after inhalation in mice. (February 2023) - Sørli, Jorid B.; Jensen, Alexander C.Ø.; Mortensen, Alicja; Szarek, Józef; Gutierrez, Claudia A.T.; Givelet, Lucas; Loeschner, Katrin; Loizides, Charis; Hafez, Iosif; Biskos, George; Vogel, Ulla; Hadrup, Niels
Abstract: Molybdenum disulphide (MoS2 ) is a constituent of many products. To protect humans, it is important to know at what air concentrations it becomes toxic. For this, we tested MoS2 particles by nose-only inhalation in mice. Exposures were set to 13, 50 and 150 mg MoS2 /m 3 (=8, 30 and 90 mg Mo/m 3 ), corresponding to Low, Mid and High exposure. The duration was 30 min/day, 5 days/week for 3 weeks. Molybdenum lung-deposition levels were estimated based on aerosol particle size distribution measurements, and empirically determined with inductively coupled plasma-mass spectrometry (ICP-MS). Toxicological endpoints were body weight gain, respiratory function, pulmonary inflammation, histopathology, and genotoxicity (comet assay). Acellular reactive oxygen species (ROS) production was also determined. The aerosolised MoS2 powder had a mean aerodynamic diameter of 800 nm, and a specific surface area of 8.96 m 2 /g. Alveolar deposition of MoS2 in lung was estimated at 7, 27 and 79 µg/mouse and measured as 35, 101 and 171 µg/mouse for Low, Mid and High exposure, respectively. Body weight gain was lower than in controls at Mid and High exposure. The tidal volume was decreased with Low and Mid exposure on day 15. Increased genotoxicity was seen in bronchoalveolar lavage (BAL) fluid cells at Mid and High exposures. ROS production was substantially lower than for carbon black nanoparticles used as bench-mark, when normalised by mass. Yet if ROS of MoS2 was normalised by surface area, it was similar to that of carbon black, suggesting that a ROS contribution to the observed genotoxicity cannot be ruled out. In conclusion, effects on body weight gain and genotoxicity indicated that Low exposure (13 mg MoS2 /m 3, corresponding to 0.8 mg/m 3 for an 8-hour working day) was a No Observed Adverse Effect Concentration (NOAEC, ) while effects on respiratory function suggested this level as a Lowest Observed Adverse Effect Concentration (LOAEC).